ESTUDIO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UN HOTEL ECOLÓGICO, EN LA ISLA ISABELA - GALÁPAGOS - Córdova Pintado, Jefferson Gustavo (2015)
This project entitled "Feasibility Study for the Implementation of a green hotel, on Isabela Island - Galapagos" proposes the idea of investing in the creation of an environmentally friendly Hotel as a solution to the problem of non-availability of infrastructure, planning and investment by the tourism industry that fits perfectly into the ecosystem of the island. The main objective of the research is to determine the feasibility of implementing an environmentally friendly hotel. With the creation of this hotel it aims to promote tourism in that district, thus generating more jobs and encouraging ecotourism in order to protect all species living on the island. For the structuring and development of the research project was necessary to apply different methods and techniques which helped develop the same in different aspects such as the realization of the framework of the question asked, from personal interviews and surveys, achieve generalize behaviors or skills among actors of tourism, analysis of the results of the market study was also performed, allowing to recognize and determine the tastes and preferences of customers and other characteristics, which should be based to offer tourist services and eventually he could perform calculations for the financial analysis and financial study. Within the market research market segment which will be directed services are established, tourists who visit the island in the period 2014 (70812 visitors). Currently 62% of this demand are using tourist services (43,903 tourists);however, this percentage 98% are really interested in making use of the service to be offered (43025 tourists). The ECOHOTEL SAMAY SA will be located in the parish of Santo Tomas de Berlanga, industry La Esperanza, 25 minutes from town (Puerto Villamil) .The installed capacity of the project was determined based on the facilities that have the hotel to cater to their clientele have a capacity of 15,652 people annually and capacity utilization of 85.38% for the year 1 13.364. processes was determined to run for the provision of services by area: in the area hosting the estimated time to provide a service unit is 32 minutes if the reservation is made via internet or phone and 21 minutes if done personally and in the area of power required in a time of 49 minutes if the service via internet or phone calls and 55 minutes if it is done personally. The facilities of the company are established according to the services that will offer the hotel; Furthermore, the distribution of the plant's service area took shape. The company was established be established under the legal name of corporation, ECOHOTEL SAMAY SA, composed of five shareholders with the capital contribution of $ 353,103.60 in total. An investment budget was calculated in order to determine the requirement of the necessary assets to enable the hotel to provide services, fixed assets with a total investment of $ 474,285.00, deferred assets: a total of $ 17,900.00, current assets working capital of $ 9,625.50 is required; in essence, the project will require a total investment of $ 519,270.00. You will be taken out with a 32% equity and 68% debt capital funded by the NFL (National Financial Corporation).Costs were determined based on the requirements for providing services in each area, in which the most influential costs are comprised of costs cousins indirect materials, direct labor and raw materials. The costs were projected for the 10 year life of the project. For the calculation of income was necessary to obtain results in unit costs per service unit and per unit of dishes in the restaurant area, where they could establish a profit margin to determine the retail price of tourism products. The unit price of the service for one year is $ 20.00 was determined. With the State of Income could know if the company will incur losses or profits in the future, the present state showed positive balances for year 1 a profit of $ 87,417.76 budgeted. The breakeven calculation for year 1 states that must sell $ $ 194,357.54 for his service, and work with an installed capacity of 71.17% this means that the company does not incur losses or profits. The cash flow allowed the company to anticipate that in the future will not get cash shortfall to meet their income and expenses. For year 1, a result of $ 121,592.00 and for the year 10 $ 149,396.63 was obtained. The NPV calculation provided delimiting the ROI, ie the hotel won $ 300,885.25 in the span of 10 years of life. The IRR of the project is the 21.46%, thus understanding that this rate is higher than the rate of 9.75% financing arranged. In calculating the cost benefit ratio indicator it was concluded that for every dollar invested in this project CTV will earn 0.35 dollar. In calculating the sensitivity analysis led to results that in the case of 5% increase in costs will not affect the project and revenue decline 5% the project has negative sensitivity to potential changes presented. Finally in the capital recovery period it will do so in a period of 4 years, 1 months and 15 days. Finally we reach the conclusion that this project is feasible and constitute a form of investment very beneficial for investors, since the gains to be profitable during its lifetime.